(untitled) (International Journal of Engineering and Computer Science, 2013)
While transmitting information over multipath channels, multiple access interference cannot be easily eliminated. However, it is possible to design detectors that estimate the channel parameters accurately. The conventional detector may be unable to recover the transmitted information from the weaker users. The need for accurate parameter estimates in the presence of multiple access interference (MAI) has led the development of joint multiuser detectors/parameter estimators. These estimates are subsequently used for subscriber location estimation. Accurate and cost effective cellular localization would enable a diverse variety of new applications in the areas of tracking and tracing, access to emergency services, increased safety, monitoring, leisure, sports and entertainment. In this paper, the detector based on divided difference Kalman filter (DDF) algorithm in a closely spaced multipath fading channel is being investigated and analyzed for asynchronous direct-sequence (CDMA). The estimated delay is used to radio location purposes. The numerical analysis augmented by extensive simulations show that the proposed DDF based detector is simpler to implement, and more resilient to near-far interference in CDMA networks and is able to track closely spaced paths.